Pengaruh Profitabilitas, Likuiditas, Struktur Aset, dan Struktur Modal terhadap Gender Direksi pada Perusahaan Sektor Industri Barang Konsumsi Primer yang Terdaftar di Bursa Efek Indonesia (2019-2023) - Kharisza, Silma (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
The small number of women on company boards of directors has become an important issue in recent years. This can be seen from the 2015 Catalyst survey, which shows that the presence of women on company boards of directors is still very small. This study aims to determine the effect of profitability, liquidity, and asset structure, and capital structure on the gender of directors in companies in the Primary Consumer Goods industry sector listed on the Indonesia Stock Exchange for the 2019-2023 period. This study is a quantitative study, where the sample taken was 22 companies. The type of data used is secondary data from the internet. The analysis method used is multiple linear regression of panel data. The results of this study indicate that Profitability, Liquidity, Asset Structure and Capital Structure simultaneously have a significant effect on the Gender of Directors listed on the Indonesia Stock Exchange, Profitability has a positive and significant effect on the Gender of Directors in consumer goods industry sector companies listed on the Indonesia Stock Exchange, Liquidity has a positive and significant effect on the Gender of Directors in consumer goods industry sector companies listed on the Indonesia Stock Exchange, Asset structure has a positive and significant effect on the gender of directors in consumer goods industry sector companies listed on the Indonesia Stock Exchange, and Capital Structure has a negative and significant effect on the Gender of Directors in consumer goods industry sector companies listed on the Indonesia Stock Exchange. Keywords: Profitability, Liquidity, Asset Structure, Capital Structure, Director Gender